Art from Belgium in Australian Public Collections. - Arnauts, Frank; Van Hellemont, Rafael (Canberra : Royal Belgian Embassy, 1998)
Claus, Emile ; Diercks, Pierre Jacques ; Maeyer, Marcel ; Magritte, René ; Meunier, Henri ; Portielje, Gérard ; Richir, Herman ; Ensor, James ; Rops, Félicien ; Alechinsky, Pierre ; Dansaert, Léon ; De Bruycker, Jules ; De Cock, Cesar ; Langaskens, Maurice ; Baugniet, Charles ; Broodthaers, Marcel ; Creten, Victor ; Delvaux, Paul ; Donnay, Auguste ; Doudelet, Charles ; Evenepoel, Henri J E ; Folon, Jean-Michel ; Masereel, Frans ; Meunier, Constantin ; Motte, Charles ; Nieuwenhuis, Jacques-Emile Edouard ; Rassenfosse, Armand ; Severin, Mark ; Singier, Gustave ; Smits, Eugène ; Stevens, Gustave ; Baertsoen, A. ; Rassenfosse, Armand ; Bury, Pol ; Lemmen, Georges ; Richir, Herman ; Ubac, Raoul ; Van Beueren, Peter ; Missone, Léonard ; Rombaux, Egide ; Vandevelde, Henry
Engels
boek
Keywords: Australië; België